Comparison of 3 Different Enucleation Techniques of Holmium Laser Enucleation of Prostate (HoLEP) - Tokatli, Zafer; Esen, Baris; Yaman, Önder; Saglam, Remzi (Urology Journal, 2020)
Purpose: To evaluate the effect of different enucleation techniques on operation time, enucleation efficacy and postoperative results. Materials and Methods: 178 HoLEP cases performed by two senior surgeons were evaluated retrospectively. All patients were evaluated for age, IPSS, preoperative PSA, prostate size, maximum flow rate (Qmax) postvoid residual volume (PVR), enucleation time, morcellation time, enucleated tissue weight, enucleation ratio (enucleated tissue weight/prostate volume) and enucleation time efficacy (enucleated weight/enucleation time). Patients were categorized into three groups according to performed enucleation techniques; Retrograde Low Tension (RLT) two-lobe, traditional three-lobe, and en bloc techniques. IPSS, Qmax, PVR and transient urine leakage (TUL) were evaluated during postoperative follow up. All preoperative, intraoperative and postoperative results were compared between 3 groups. Results: Mean age was 70.52 (52-85) years. Baseline data were comparable between groups. Enucleation time was significantly shorter in RLT two-lobe (median; 50, 60 and 60 min; RLT two-lobe, traditional three-lobe, and en bloc HoLEP techniques, respectively. (P = .031). Morcellation time was comparable between groups (P = .532). No significant difference was observed between morcellated prostate weights (P = .916) Significant improvements in IPSS, Qmax, and PVR were noted in all groups (P < .001). TUL was significantly increased in en bloc technique (P = .034). Postoperative stricture rates were similar between groups. (P = .769) Conclusion: Shorter enucleation time was observed in the RLT HoLEP technique and increased TUL rate was observed in the en bloc technique.